The Effect of Manager's Commitment, Training, and Sustainable Improvement on Construction Project Performance in the Pandemic Era - Barri, Ahmad; Budiandru (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
The purpose of this study was to determine The Effect of Manager Commitment, Training, and Continuous Improvement on PT Harvest City Construction Project Performance in the Pandemic Era. The method used in this study is a quantitative method with primary data types. The sampling technique used was purposive sampling with a sample of 218 construction workers with 126 respondents. The techniques employed for data management and analysis include external model analysis (measurement model) and internal model analysis (structural model) utilizing the SmartPLS 3 Multivariate Structural Equation Model (SEM) approach. Partially the results of this study indicate that the manager's commitment has a P-value of 0.106 > 0.05, so it can be interpreted that the manager's commitment does not affect project performance, training has a P-value of 0.029 < 0.05, so it can be interpreted that training effect on project performance and continuous improvement has a P-Value of 0.005 < 0.05, so it can be interpreted that continuous improvement has an effect on project performance. Concurrently, this investigation achieved an R-Square (R2) value of 0.81, equivalent to 81%. This indicates that the project performance variable is influenced by manager commitment, training, and continuous improvement to the extent of 81%.